Kraton Jogja and Covid-19: When Pandemic Brings Traditional Culture Closer to Millennials Around The World - Hakim, Lutfi Maulana; Gondohutami, Erwita Danu (Mahesa Research Center, 2023)
Karaton Ngayogyakarta Hadiningrat which now mostly recognized by the name Kraton Jogja in community, is the largest cultural-based institution in Yogyakarta. So, Kraton Jogja has duty to maintain, preserve, and develop traditional arts and culture. COVID-19 pandemic that has swept across the world, has forced many offline activities to be postponed or cancelled. Kawedanan Hageng Punakawan Kridhamardawa as the department tasked with preserving and developing Javanese arts was also affected. Their activities are limited even though they have to be present in society, that is now dominated by the millennial generation. By using the concepts of globalization and global village, this study aims to find out how the use of various digital media channels can be a solution in the midst of limitations. This research was conducted using qualitative methods through interviews, observation and literature study. The findings in this study explore a variety of content presentation innovations on the official social media of Kraton Jogja. The result shows that the use of digital media in the midst of a pandemic can actually cut through distance, space and time, so that traditional arts and culture can be enjoyed by audiences across generations from all over the world.